ANALISIS PENGGUNAAN MEDIA PEMBELAJARAN KOMIK BERBASIS KEARIFAN LOKAL SASAK DALAM MEMUDAHKAN KEGIATAN BELAJAR SISWA PADA MATERI IPS KELAS IV DI SDN GANTANG - Arini, Soning; Hakim, Mansur; Tahir, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Comic media is a learning tool that uses pictorial stories (comics) to help students understand the subject matter in a soothing way. This study aims to determine the use of comic learning media based on Sasak local wisdom in Social Science materials. This study uses a qualitative descriptive approach. The subject of the study is the fourth grade students of SD Negeri Gantang, while the object of this study is the use of comic learning media based on Sasak local wisdom. The data collection techniques used are observation, interviews, and documentation. The data was analyzed by going through three stages, namely the preparation stage, the implementation stage and the processing stage. The results of this study show that the use of comic media based on Sasak local wisdom makes it very easy for students to understand social studies material regarding cultural diversity. Researchers involve students directly in learning activities so that students are active and not bored in teaching and learning activities. In social studies learning using comic media, it can attract students' interest in learning. This can be seen when comic media based on Sasak local wisdom is implemented in the classroom.